Genome-wide analysis and characterization of TPD1 family proteins in pearl millet (Cenchrus americanus): Insights into reproductive regulation and phytohormone responses. - Zainab M Almutairi (PLoS ONE)
The Tapetum Determinant 1 (TPD1) family proteins are known to play a crucial role in the regulation of reproduction in plants, including Cenchrus americanus (pearl millet). However, members of TPD1 family proteins have not been fully identified. The current study aims to identify and characterize the TPD1 family proteins in Cenchrus americanus (L.) Morrone. Seven transmembrane proteins (from 127 to 172 aa) comprising TPD1 domain were identified via genome-wide mining. Analysis of gene expression during developmental stages revealed high expression of four CaTPD1s in reproductive organs. Treatment with phytohormones showed that the expression of CaTPD1s was repressed by hormone treatments except CaTPD1_Ch4.1 and CaTPD1_Ch4.3 which are highly expressed in response to brassinolide and auxin, respectively. Screening of cis-elements in the promoter of CaTPD1s revealed various cis-elements related to phytohormone regulation, wound response, abiotic stress defense, and light response. The phylogenetic tree revealed distinct clustering of CaTPD1_Ch6 and CaTPD1_Ch5 among the other CaTPD1s, which revealed close relationships with the orthologs from Arabidopsis and rice that are known to have a critical role in tapetum development and pollen and ovule production. Hence, this study affirms the role of the CaTPD1s genes in the growth and reproduction during pearl millet developmental stages.